Heterozygous mutation of cysteine(528) in XPO1 is sufficient for resistance to selective inhibitors of nuclear export - Neggers, Jasper Edgar (Oncotarget, 2016)
Exportin-1 (CRM1/XPO1) is a crucial nuclear export protein that transports a wide variety of proteins from the nucleus to the cytoplasm. These cargo proteins include tumor suppressors and growth-regulatory factors and as such XPO1 is considered a potential anti-cancer target. From this perspective, inhibition of the XPO1-mediated nuclear export by selective inhibitor of nuclear export (SINE) compounds has shown broad-spectrum anti-cancer activity. Furthermore, the clinical candidate SINE, selinexor, is currently in multiple phase I/II/IIb trials for treatment of cancer. Resistance against selinexor has not yet been observed in the clinic, but in vitro selection of resistance did not reveal any mutations in the target protein, XPO1. However, introduction of a homozygous mutation at the drug's target site, the cysteine 528 residue inside the XPO1 cargo-binding pocket, by genetic engineering, confers resistance to selinexor. Here we investigated whether this resistance to selinexor is recessive or dominant. For this purpose we have engineered multiple leukemia cell lines containing heterozygous or homozygous C528S substitutions using CRISPR/Cas9-mediated genome editing. Our findings show that heterozygous mutation confers similar resistance against selinexor as homozygous substitution, demonstrating that SINE resistance can be obtained by a single and dominant mutation of the cysteine(528) residue in XPO1.